The effect of the financing structure on the return on the market share in Saudi companies An Empirical Study - Asiri, Fatimah Mohammad (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the influence of the financing structure on the return of the market share in Saudi corporations/companies. The study applied the descriptive-analytical approach, and the study population consisted of some joint-stock companies in the Saudi stock market, where the study sample consisted of (75) companies in five productive sectors where concentration was made on the following sectors: (basic materials, long-term commodities, energy, food production, capital goods). Method of the comprehensive survey was used for all companies. The data was analyzed using the Panel Data method through the STATA program. The study concluded several findings, the most important of which are that short-term debt (liabilities) have a negative impact on the return on the market share, as increasing short debts (liabilities) lead to a decrease in the return on the market share, and that long-term debt (liabilities) have no effect on the return on the market share, and equity has a negative impact on the return on the market share, as the increase in financing through equity leads to a decrease in the return on the market share. The study recommended the necessity of diversification between sources of financing and not limited to debt and long & short-term liabilities only. It also recommended conducting such a study on other sectors or conducting it on the whole market which may result in improving results, and also recommends expanding the time period more than five years, which may lead to improve results.